Adaptation to environmental temperature in divergent clades of the nematode Pristionchus pacificus. (1st August 2022) - Leaver, Mark; Moreno, Eduardo; Kayhan, Merve; McGaughran, Angela; Rödelsperger, Christian; Sommer, Ralf J.; Hyman, Anthony A.
Abstract: Because of ongoing climate change, populations of organisms are being subjected to stressful temperatures more often. This is especially problematic for ectothermic organisms, which are likely to be more sensitive to changes in temperature. Therefore, we need to know if ectotherms have adapted to environmental temperature and, if so, what are the evolutionary mechanisms behind such adaptation. Here, we use the nematode Pristionchus pacificus as a case study to investigate thermal adaptation on the Indian Ocean island of La Réunion, which experiences a range of temperatures from coast to summit. We study the evolution of high‐temperature tolerance by constructing a phylogenetic tree of strains collected from many different thermal niches. We show that populations of P. pacificus at low altitudes have higher fertility at warmer temperatures. Most likely, this phenotype has arisen recently and at least twice independently, consistent with parallel evolution. We also studied low‐temperature tolerance and showed that populations from high altitudes have increased their fertility at cooler temperatures. Together, these data indicate that P. pacificus strains on La Réunion are subject to divergent selection, adapting to hot and cold niches at the coast and summit of the volcano. Precisely defining these thermal niches provides essential information for models that predict the impact of future climate change on these populations.